2012
DOI: 10.1111/j.1600-079x.2012.00980.x
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin‐induced autophagy protects against human prion protein‐mediated neurotoxicity

Abstract: Melatonin has neuroprotective effects in the models of neurodegenerative disease including Alzheimer's and Parkinson's disease. Several studies have shown that melatonin prevents neurodegeneration by regulation of mitochondrial function. However, the protective action of melatonin has not been reported in prion disease. We investigated the influence of melatonin on prion-mediated neurotoxicity. Melatonin rescued neuronal cells from PrP(106-126)-induced neurotoxicity by prevention of mitochondrial dysfunction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 43 publications
3
54
1
Order By: Relevance
“…Our results strongly suggest the contribution of the melatonin receptor in ovine classical scrapie pathology, even in the early phase of the disease and in different brain regions; therefore, melatonin may be a good candidate target for future prion disease therapies. In accordance with our suggestion, a recent report has shown that melatonin-induced autophagy protects against prion protein-mediated neurotoxicity [77]. …”
Section: Discussionsupporting
confidence: 92%
“…Our results strongly suggest the contribution of the melatonin receptor in ovine classical scrapie pathology, even in the early phase of the disease and in different brain regions; therefore, melatonin may be a good candidate target for future prion disease therapies. In accordance with our suggestion, a recent report has shown that melatonin-induced autophagy protects against prion protein-mediated neurotoxicity [77]. …”
Section: Discussionsupporting
confidence: 92%
“…Although during the last decade different studies have related melatonin with autophagy regulation in different disease models, like cardiac and brain ischemia or subarachnoid hemorrhage, kainic acid–induced toxicity, prion peptide–induced toxicity, Parkinson's disease, traumatic brain injury, or aging models, little is known about its implication in AD, and more specifically in tauopathies. Melatonin is widely known to regulate the autophagy‐lysosome machinery at very different levels .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some of the apoptotic pathway genes we detected among the potential RORa target genes were shown to be regulated by melatonin. While Bcl2 pathway-related gene Atg5 was shown to be responsible for neuroprotective role of melatonin (30), cytochrome c pathway-related gene Nlrp3 was found to be involved in anti-inflammatory role of melatonin (31). Though the latter study focused on inflammation and not apoptosis, it revealed the involvement of RORa and melatonin in Nlrp3-NFkappaB pathway.…”
Section: Discussionmentioning
confidence: 99%